Tris(1,3-dichloro-2-propyl) phosphate Exposure During Early-Blastula Alters the Normal Trajectory of Zebrafish Embryogenesis - Dasgupta, Subham (Environ Sci Technol, 2018)
Tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) is an organophosphate flame retardant used around the world. Within zebrafish, we previously showed that initiation of TDCIPP exposure during cleavage (0.75 h post-fertilization, hpf) results in epiboly disruption at 6 hpf, leading to dorsalized embryos by 24 hpf – a phenotype that mimics the effects of dorsomorphin (DMP), a bone morphogenetic protein (BMP) antagonist that dorsalizes embryos in the absence of epiboly defects. The objective of this study was to 1) investigate the role of BMP signaling in TDCIPP-induced toxicity during early embryogenesis; 2) identify other pathways and processes targeted by TDCIPP; and 3) characterize downstream impacts of early developmental defects. Using zebrafish as a model, we first identified a sensitive window for TDCIPP induced effects following exposure initiation at 0.75 hpf. We then investigated the effects of TDCIPP on the transcriptome during the first 24 h of development using mRNA and amplicon sequencing. Finally, we relied on whole mount immunohistochemistry, dye based labeling, and morphological assessments to study abnormalities later in embryonic development. Overall, our data suggest that initiation of TDCIPP exposure during early blastula alters the normal trajectory of early embryogenesis by inducing gastrulation defects and aberrant germ layer formation, leading to abnormal tissue and organ development within the embryo.